DAMPAK PEMBERIAN BANTUAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP KESEHATAN IBU HAMIL: ANALISIS PERBANDINGAN DAERAH PENERIMA DENGAN BUKAN PENERIMA - , AGHISNI HARDEWINTA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The Indonesian CCT called Program Keluarga Harapan(PKH) is one of governments program that aims to alleviate poverty through health and education. PKH provides funding assistance to pregnant women with the condition of pregnant women should comply with obligation as participantsof PKH. Yet, evaluation onits effectiveness is limited. Objective: To determine differences in impact of Indonesian CCT grants to the health status of pregnant women. Methods: This study was an observational study with cross-sectional design, the two groupswere subjects who receivedPKHand non-recipient ofPKH. Sosiodemographic datawere collectedby using questionnaires. Anaemia and chronic energy deficiency were identified by using hemocue and upper arm circumference measurements. To determine maternal perception ofPKH anin-depth interview with recipient were conducted. Analysis of the data used Mann Whitney test statistic. Results: In this study, the number of subjects who have high levels of iron tablet intake compliance was high in both groups of subjects as much as 66.67%. For anemia status, both groups of study subjects also have the same number is 56.67%. status for the group receiving PKH with chronic energy deficiency as much as 10%, while in the group not receiving PKH who suffered chronic energy deficiency as much as 13.33% .The result of different test by Mann Whitney test on the compliance variable iron tablet consumption, anaemia status and the status of the indicates that there is no significant difference between the group and the group not receiving PKH PKH recipients (p> 0.05). significance value between each independent variable with sequentially dependent variable was p = 1.000, p = 1.000, and p = 0.492. Conclusions: There were no significant differences between groups of recipients PKH and non recipients of PKH on adherenceiron tablet consumption, anaemia status and the status of chronic energy malnutrition.